IMPROVEMENT OF THE METHODOLOGY OF TRAINING MASTERS OF TECHNICAL SPECIALIZATION FOR SCIENTIFIC RESEARCH ACTIVITIES (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2025)
The article reveals the essence and content of the pedagogical model for developing the readiness of master's students for research activities.